Study on the Permeability Change Characteristic of Gas-Bearing Coal under Cyclic Loading and Unloading Path. (15th April 2021) - Wang, Fakai; Li, Xuelong; Cui, Bo; Hao, Jian; Chen, Peng
Abstract : Using the self-developed three-axis servo fluid-solid coupling system with gas-solid coupling of gas-bearing coal, the variation law of the permeability of gas coal under the stress cycle loading and unloading path was studied. The qualitative and quantitative relationships between permeability, axial force, and radial stress of gas-bearing coals were established, and the variation law of permeability of gas-bearing coals was discussed. The results show that (1) different cyclic loading and unloading stress paths correspond to the permeability characteristics of different gas-bearing coals. (2) Permeability of gas-bearing coal decreases with the increase of axial stress and radial stress, and it has a logarithmic function with axial stress and radial stress. This shows that axial stress and radial stress are important factors affecting the permeability characteristics of gas-bearing coal. (3) Under the same stress loading and unloading conditions, the axial stress is less than radial stress on the permeability of gas-bearing coal. In the cyclic loading and unloading axial stress process, the permeability of the gas-bearing coal varies by a smaller extent than the cyclically unloaded confining force. (4) The cumulative damage rate of gas-bearing coal under axial stress gradually increases with the increase of the number of cycles of loading and unloading, and the rate of the cumulative damage rate of permeability is less than the corresponding rate of radial stress.